Endométriose et travail, un calvaire au féminin - Poissonnier, Gaétane (Alternatives Economiques, 2021)
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; corps; cours; discipline; endométriose; europe; france; inégalités; justice reproductive; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Imaginary women, imaginary audience: Gender and top 40 radio in Montréal - Maki, Christine (Women in radio: Unfiltered voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audience. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit women’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; communication; culture populaire; discipline; discours dominant; genre; montréal; périodes historiques; radio; ressource en ligne; régions géographiques; sexisme; stéréotypes de genre; systèmes d'oppressions